Psychological well-being and anxiety among relatives of Mexican cancer patients: Two models - García Cadena, Cirilo Humberto (Universidad Autónoma de Tamaulipas, 2020)
The psychopathological model of mental health emphasizes dimensions such as depression and anxiety. The dual model however includes positive traits such as optimism and self-esteem. The current study compared both models to show which one better predicts psychological wellbeing as well as anxiety. The procedure utilized in this study included calculating a mental health index that combined optimism, self-esteem, depression and perceived stress scores. The sample for convenien-ce consisted of 350 relatives of cancer patients. Their mean age was M = 39.87 years, SD = 14.87. Structural equation modeling was used to measure the effects of mental health over psychological well-being and anxiety. Findings reveal that both models produce similar size effects (> 0.26) of the explained variances. The dual model however has a greater capacity to predict psychological well-being (.65 versus .44) and anxiety (.46 versus .38). Finally, the article discusses implications of the dual model for diagnosis, interpretation and interven-tion.